Strategy to Increase Employee Engagement Through Learning Agility and Organizational Citizenship Behavior in the National Defense Agency at the District Level - Hamdani, Maulana; Pratminingsih, Sri Astuti (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Kuningan, 2025)
This study aims to analyze the effect of learning agility on employee engagement with organizational citizenship behavior (OCB) as a mediating variable at the National Land Agency (BPN) in one of the districts in West Java Province. The research method used is descriptive verification with a quantitative approach, involving 65 employees as respondents through a saturated sampling technique. Data were collected using a structured questionnaire and analyzed using path analysis and the Sobel test to test the mediation effect. The results show that learning agility has a significant effect on employee engagement, both directly and indirectly through OCB as a mediator. The R Square value of 0.932 indicates that the combination of learning agility and OCB explains 93.2% of the variation in employee engagement. This finding emphasizes the importance of managerial strategies that encourage adaptive learning and strengthen organizational citizenship values in creating a productive, collaborative, and responsive work environment to change. This study provides a practical contribution to the development of public sector HR policies oriented towards increasing employee engagement through strengthening a learning-based and collaborative work culture